Concurrent administration of trastuzumab and anthracyclines as adjuvant regimen for HER2-positive breast cancer: a randomised controlled trial - Shen, Songjie (Oncotarget, 2017)
BACKGROUND: The regimen of concurrent administration of trastuzumab and anthracyclines in the adjuvant treatment of breast cancer has never been evaluated prospectively for fear of cardiac toxicity. METHODS: Patients with HER2-positive operable breast cancer were randomised to receive adjuvant treatment with concurrent or sequential administration of trastuzumab and anthracyclines. Cardiac monitoring was scheduled at baseline and every 3 months after the first dose of trastuzumab. The primary study endpoint was cardiac safety. Secondary endpoints were disease-free and overall survival. RESULTS: From 2011 to 2014, 201 participants were enrolled and randomised. The median follow-up time was 42 months. Nineteen patients (19.4%) in the concurrent group and 22 patients (22.4%) in the sequential group met the criteria for cardiac events with non-significant difference (P=0.598). There was no difference in the mean LVEF between the two groups at the baseline and at 3, 6, 9, 12, and 24 months after the first dose of trastuzumab. No case of congestive heart failure or cardiac death occurred. The differences between the efficacies of the two regimens, defined by disease-free or overall survival, were not significant. CONCLUSIONS: Concurrent administration of trastuzumab and anthracyclines is a safe adjuvant regimen and it provides evidence for further clinical trials.